Algebra 1

Published by Prentice Hall
ISBN 10: 0133500403
ISBN 13: 978-0-13350-040-0

Chapter 7 - Exponents and Exponential Functions - 7-4 More Multiplication Properties of Exponents - Practice and Problem-Solving Exercises - Page 437: 61



Work Step by Step

RECALL: (i) $(a^m)^n = a^{mn}$ (ii) $(ab)^m=a^mb^m$ (ii) $a^m \cdot a^n =a^{m+n}$ (iv) $a^0=1, a\ne0$ Use rule (i) and rule (ii) above to obtain: $=(-2)^3a^{2\cdot3}b^3 \cdot a^3b^3 \\=-8a^6b^3 \cdot a^3b^3$ Use rule (iii) above to have: $=-8a^{6+3}b^{3+3} \\=-8a^9b^6$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.